Vocabulary learning through listening: Comparing L2 explanations, teacher codeswitching, contrastive focus-on-form and incidental learning - Zhang, Pengchong; Graham, Suzanne (Language teaching research : LTR, 2020)
This study explored the teaching and learning of vocabulary through listening among 137 senior high-school learners of English as a foreign language (EFL) in China. It compared different types of Lexical Focus-on-Form delivered to four treatment groups: post-listening vocabulary explanations in the L2; codeswitched explanations; explanations providing additional crosslinguistic information (Contrastive Focus-on-Form; CFoF); and no explanations (NE). It also investigated the impact of the intervention on learners’ listening comprehension. Learners completed aural vocabulary tests at pre-, post- and delayed post-test and listening assessments at pre- and post-test. For short- and long-term vocabulary acquisition, the three groups receiving explanations significantly outperformed the NE group. Gains for the CFoF group were significantly greater than for the L2 and Codeswitching groups, for both short-term and long-term learning. For listening comprehension, only the NE group made significant improvement from the pre-test to the post-test, as well as making significantly greater pre- to post-test improvement than the CFoF and the L2 groups did. The article concludes by discussing these findings in relation to theories of vocabulary acquisition and listening comprehension, as well as their pedagogical implications.